Recording Vital and Laboratory Parameters and the Risk of Death in Children Admitted to First- and Second-Level Hospitals for Emergency Medical Care: A Case-Control Study - Dmitry V. Prometnoy; Yuriy S. Aleksandrovich; Konstantin V. Pshenisnov; Helen D. Teplyakova; Sergey A. Razumov (Вопросы современной педиатрии, 2019)
Background. Diagnostic mistakes due to incomplete examination of patients are the leading cause of death. The prevalence of such mistakes and their association with treatment outcomes in our country remain uninvestigated. Objective. Our aim was to study the frequency of recording vital and laboratory parameters and its relationship with death in children admitted to a hospital for emergency medical care. Methods. In our case-control study we analysed the data of medical records of an inpatient (Form 003/u) — patients for intensive care at the age of 0–17 years who were admitted to first-level (n = 13) and second-level (n = 5) hospitals of the Rostov Region (except for Rostov-on-Don) in 2006–2017. We considered the frequency of recording vital (heart rate, respiration rate; blood pressure; oxygen saturation of arterial blood; body temperature) and laboratory (blood count, haemoglobin, hematocrit, total protein, glucose, urea, creatinine, pH, pCO2, pO2, BE, sodium and potassium levels) parameters upon admission to in-patient hospital and when transferred to the intensive care unit (ICU). The association of the frequency of recording these parameters with hospital outcome was assessed using multivariate logistic regression analysis adjusted for the effect of confounders (consultation by a resuscitationist of the resuscitation and consultation centre; the level of healthcare facility; admission time; the presence of infectious diseases and diseases that occurred in the perinatal period; the level of consciousness; the duration of the underlying disease before admission; the method of admission to a healthcare facility). Results. We studied the data of 61 children with a favourable (discharged from healthcare facilities) and 90 children with a fatal outcome in the in-patient hospital (76 — in the ICU). A fatal outcome in the in-patient hospital was associated with records of BE [odds ratio (OR) 3.25; 95% confidence interval (CI) 1.25–8.46)], total protein level (OR 0.19; 95% CI 0.05–0.79), urea (OR 0.24; 95% CI 0.06–0.87) and creatinine (OR 0.23; 95% CI 0.08–0.67) upon admission. A fatal outcome in the ICU was associated with records of systolic (OR 0.36; 95% CI 0.14–0.94) and diastolic (OR 0.30; 95% CI 0.12–0.80) blood pressure, SpO2 (OR 0.38; 95% CI 0.15–0.93) and body temperature (OR 0.32; 95% CI 0.11–0.90) upon admission to the unit. Conclusion. The association of the outcome with recording of vital (blood pressure, SpO2 and body temperature upon admission to the ICU) and laboratory (BE, total protein, urea, creatinine upon admission to a healthcare facility) parameters in children admitted to a hospital for emergency medical care indicates the need to control their clinical and paraclinic examination. A more complete examination of these children may be a reserve for reducing hospital mortality.